An analysis of specialized phraseological verbs in Museum Studies - Joan Casademont, Anna (2020)
This article aims at contributing to the description of phenomena linked to dynamicity in specialized discourse. Specifically, we analyze the behaviour of phraseological verbs in the domain of museology and museography in a Spanish corpus using Termostat (Drouin, 2003). We start with the characterization of phraseological verbs transmitting specialized knowledge proposed initially by Lorente (2007) and extended by AUTOR/A (2008, 2014). Our analytical method is built on the one used by AUTOR/A (2008, 2014, 2017, 2018). Aside from the characterization of meanings related to the domain of Museum Studies (an aspect that will allow us to lexicographically guide work related to terminographical compilation for Museum Studies), our goal is to confirm that the proposal of relevant elements in the distribution of terminological value in phraseological verbs is appropriate in a domain and in a romance language differing from the ones specified in AUTOR/A (2008, 2014).